PENDAMPINGAN PEMBELAJARAN DARING BERBASIS SINKRON DAN ASINKRON MAYA BAGI GURU-GURU SEKOLAH MENENGAH KEJURUAN KABUPATEN TABANAN - Supriana, I.W.; Putri, L.A.A.R.; Giri, G.A.V.M.; Mahendra, I.B.M. (Buletin Udayana Mengabdi; Vol 22 No 1 (2023): Buletin Udayana Mengabdi, 2023)
Technological developments are increasingly rapid and almost touch various fields of life, not least in the field of education. The most visible impact in the field of education is the Covid-19 pandemic, which until now the learning process is still carried out online. Likewise, the learning process at the Margaranan Tabanan Tourism Vocational School is currently mostly through WA groups. The use and utilization of technology is very important as a learning medium in the Covid-19 pandemic. Synchronous and asynchronous learning models are learning models that are carried out online by utilizing internet network technology so that the learning process can still be packaged effectively and innovatively. In this service, training and mentoring will be carried out for teachers to carry out virtual synchronous and asynchronous learning by using the Google application (Google Meet, Google Classroom, Google Form) and Edmodo. The training was conducted for 20 teachers. Based on the training that has been carried out, the virtual synchronous and asynchronous-based online learning process has been successfully implemented and most of the participants are able and ready to implement online learning with online applications that have been taught. Keywords: Training, Technology, Vocational High School, Online, Teacher